Energy service market evaluation by Bayesian belief network and SWOT analysis: case of Turkey - Acuner, Ebru; Cin, Rabia; Onaygil, Sermin (Springer Science and Business Media LLC, 2021)
In Turkey, the energy service market has been growing since 2008 and one of the main actors is energy efficiency consulting (EVD) companies. As of January 2020, 45 EVD have been active in the market. To analyze the current situation of the energy service market, a questionnaire was prepared and sent to all EVD companies and 13 of them responded. In the questionnaire, the main contents can be listed as control authority, sub-sectors for the energy efficiency audits and implementation projects, possible measures determined after audits, the main focus of implementation projects, and main financing sources in audits and implementation projects. The obtained answers were explored by Bayesian belief networks (BBN) through Netica modelling program. According to BBN analysis, in the current situation, the success of the energy service market is about 58%. Considering both the improvements in the regulations and the results of the survey together with BBN, SWOT analysis of the Turkish energy service market was made. Depending on the strengths, weaknesses, opportunities, and threats, in order to improve the success, it is clarified that implementation projects should be increased both in number and quality. National Energy Efficiency Fund should be formed and it is declared that energy performance contracts (EnPCs) should be more actively used together with measurement and verification for more reliable market formation.